Bounding the Number of Minimal Transversals in Tripartite 3-Uniform Hypergraphs - Bazin, Alexandre; Beaudou, Laurent; Kahn, Giacomo; Khoshkhah, Kaveh (Discrete mathematics and theoretical computer science, 2023)
We focus on the maximum number of minimal transversals in 3-partite 3-uniform hypergraphs on n vertices. Those hypergraphs (and their minimal transversals) are commonly found in database applications. In this paper we prove that this number grows at least like 1.4977^n and at most like 1.5012^n.